A Nonintrusive Flow Rate Sensor Based on Microwave Split-Ring Resonators and Thermal Modulation - Niksan, Omid; Jain, Mandeep Chhajer; Shah, Aaryaman; Zarifi, Mohammad Hossein (IEEE transactions on microwave theory and techniques, 2022)
Microwave sensors offer noncontact solutions for flow rate measurements, central to various applications in pharmaceutics, chemical analysis, and biomedicine. The challenge, however, remains for microwave flow rate sensing of uniform liquids, where different flow rates do not lead to any permittivity or conductivity variations. In this work, we propose a noncontact, nonintrusive microwave sensor, capable of measuring the flow rate of uniform liquids. This sensor comprises a microwave split-ring resonator (SRR) integrated with a temperature modulation technique. The sensor operates based on the change in the dielectric properties of the liquid inside the channel, induced by local delivery of thermal energy. Different flow rates affect the exposure time of the liquid to thermal energy, which alters its permittivity and loss tangent, consequently changing the response of the SRR. The SRR with the integrated fluidic channel is designed to operate at 4.6 GHz with a resonant amplitude of −6.8 dB and a Q -factor (−3 dB) of 98. By monitoring the S_{21} (dB) response, flow rates ranging from 1 to 40 mL/h are differentiated. The S_{21} (dB) response's achieved sensitivity to different flow rates is \vert 0.02\vert dB/mL/h. The proof of concept is successfully evaluated using water and isopropanol as two standard liquids. The results indicate the potential of the proposed nonintrusive flow rate sensing method in various applications, such as drug delivery and chemical sample preparation.